Brain and Mind - Cees van Leeuwen (Philosophia Scientiæ)
The debate on mind–brain relationships has been centered on issues of free will. I investigate the debate and conclude that the neurosciences neither have compelling methodological, ontological, theoretical reasons, nor empirical reasons to reject the notion of free will. At the same time, I concede that the issue is highly contentious, both in science and society. The problem resides in the clash between scientific notions of the brain and pre-scientific notions of mind. I therefore propose to look at mind–brain relationships on a more sound, and uncontroversial, empirical basis, which can be found in psychophysics. I discuss two instances in which the content of a psychophysical experience, and its dynamics, correspond to brain dynamics. In one case, the correspondence is a one:one type-identity, in the other it is a case of radical multiple instantiation: several radically different types of brain activity give rise to the same perceptual dynamics. These two examples illustrate that although type identity is possible, it may often be highly contextualized. Mind–brain relationships are therefore more likely to be conquered one by one rather than established wholesale.